2020
DOI: 10.1053/j.ajkd.2019.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Diagnosed Nonsyndromic Nephronophthisis in Australian Families Caused by Biallelic NPHP4 Variants

Abstract: There is increasing appreciation of nephronophthisis (NPHP) as an autosomal recessive cause of kidney failure and earlier stages of chronic kidney disease among adults. We identified 2 families with presumed adult-diagnosed nonsyndromic NPHP and negative diagnostic genetic testing results from our Renal Genetics Clinic. Both had 2 affected siblings without extrarenal phenotypes. After informed consent, research whole-genome sequencing was undertaken. Biallelic NPHP4 variants were identified in trans and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Two-thirds of all NPH cases have no clearly identifiable gene mutation [ 80 ]. Causative genes that are representative of adolescent/adult NPH include: NPHP3 , NPHP4 , and NPHP9 / NEK8, but some cases of NPH do not clearly match up with any of these genes [ 80 , 81 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Cystic Kidney Diseases That Require a Differential Diagnosis...mentioning
confidence: 99%
“…Two-thirds of all NPH cases have no clearly identifiable gene mutation [ 80 ]. Causative genes that are representative of adolescent/adult NPH include: NPHP3 , NPHP4 , and NPHP9 / NEK8, but some cases of NPH do not clearly match up with any of these genes [ 80 , 81 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Cystic Kidney Diseases That Require a Differential Diagnosis...mentioning
confidence: 99%
“…NPHP does not have a gender predisposition and accounts for 10-25% and ~5% of all children in ESRD in Europe and North America, respectively [13]. Bollee et al [14], Hoefelle et al [15], and Hudson et al [16] showed new diagnosis of NPHP in adults with chronic kidney disease (CKD), despite the diseases likely being present from childhood.…”
Section: Epidemiologymentioning
confidence: 99%
“… 7 Nephronophthisis exhibits significant variability, even within families, and genetic diagnosis has furthered our understanding in adult CKD. 8 APOL1 G1/G2 have been linked with progression to end-stage kidney disease with focal segmental glomerulosclerosis and lupus nephritis in African American populations. 9 Genes involved in biological pathways contributing to the major risk factors for progression of CKD such as hypertension and diabetes are of particular interest.…”
mentioning
confidence: 99%